PENEGAKAN HUKUM PIDANA ISLAM (JINAYAH) DI PROVINSI NANGGROE ACEH DARUSSALAM - Surbakti, Natangsa (Jurnal Media Hukum, 2010)
The research aims at examining the characteristics of Islamic criminal law enforcement, co-existence of Islamic justice system (sharia law) and criminal justice system, and the factors inhibiting law enforcement in the Nanggroe Aceh Darussalam (NAD) province. The method employed in this research is normative empirical using qualitative data analysis technique. The result of the research shows that certain types of crime that become the competence of the Islamic judicial is based on provincial regulations called Qanun; therefore, the criminalization that occurs do not reduce the jurisdiction of civil court. Moreover, the result of the research also shows that the various factors which theoretically are known as factors supporting law enforcement are not working properly.Key words: law enforcement, Islamic criminal law, Qanun, Islamic justice system